GEOLOGY AND STATIC RESERVOIR MODELING OF PARASEQUENCE INTERVAL A (FS-4) AND B (FS-5), TALANG AKAR FORMATION, MIR FIELD, ASRI BASIN, SOUTHEAST SUMATERA - Iqbal Ramadhan, Muhammad
Widuri Field is a faulted anticline located in Tertiary back arc basin, Asri Basin, Southeast Sumatera.Widuri Field was drilled for the first time in 1988, precisely in the sandstone reservoir of Talang Akar Formation. The previous research on Widuri Field were not utilizing well data and 3D seismic data for identification of reservoir distribution, so reservoir characterization and modeling is an appropriate research to understand reservoir distribution in the MIR Field. This research focuses on reservoirs located in the parasequence interval A (FS-4) and B (FS-5) which are two of the six productive reservoirs in the MIR Field. This research aims to characterize and model reservoirs by integrating core rock description, wire line logs, biostratigraphy, well test, and 3D seismic data. The methods include analysis of facies, biostratigraphy, and depositional environment; sequence stratigraphic; depth structure mapping; reservoir geometry; facies and petrophysical modeling; and hydrocarbon in place estimation. Parasequence interval A (FS-4) and B (FS-5) are composed of nine facies, Sm, Spo, Sh, SFl, SFh, Flh, Fln, Fm, and C. Interval A (FS-4) represents a fluvial depositional environment with 3 facies associations which are fluvial channel, floodplain, swamp. Meanwhile, interval B (FS- 5) represents a fluvio-tide delta depositional environment with 3 facies associations which are distributional channel, tidal flat, and swamp. Biostratigraphy data shows a last occurrence of Late Oligocene pollen fossil and first occurrence of Early Miocene foraminifera fossil represent gradual changes in the depositional environment from terestrial to transitional. Reservoir geometry and reservoir facies distribution are described in geometric analysis, sequence stratigraphy, and three-dimensional seismic which show the direction of deposition with a northwest-southeast trend. The main structure in the MIR Field is a faulted anticline with southwest – northeast trend direction. Sequence stratigraphy of interval A (FS-4) and B (FS-5) in Talang Akar Formation are predominantly composed of parasequence with a fining upward stratigraphic pattern with retrogradation stacking patterns indicating a dominant transgressive system tract process. Reservoir A (FS-4) with facies association of fluvial channel has a width of ±250 m, while reservoir B (FS-5) with facies association of distributary channel has a width of ±275 m. Petrophysical property analysis shows the cutoff limit for volume of shale 0.696; effective porosity 0.08; and water saturation 0.552. Both reservoirs comply the cutoff limit value which has the potential for hydrocarbon content in the form of oil. Static reservoir modeling was carried out to model facies and petrophysics as well as estimate the hydrocarbon in pace (OOIP). The results of the estimation show that the amount of hydrocarbon in place in reservoir A (FS-4) is 28.1 MSTB and Reservoir B (FS-5) is 121.1 MSTB.